PENGARUH PENERAPAN E-SAMSAT, SANKSI PAJAK DAN PELAYANAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KOTA BATAM - Sholikah, Kamilatus; Purba, Mortigor Afrizal (LPPM Universitas Putera Batam, 2021)
The number of motorized vehicles in Batam City has always increased every year. The increase in the number of motorized vehicles was not accompanied by an increase in taxpayer compliance. The purpose of this study is to analyze the effect ofthe application e-SAMSAT, tax sanctions and taxation services on motor vehicle taxpayer compliance in Batam City either partially or simultaneously. Where the application of e-SAMSAT, tax sanctions and taxation services are independent variables and motor vehicle taxpayer compliance as the dependent variable. The number of samples is 100 respondents. The primary data collection method used was a survey method using a questionnaire. The results of the T test and F test data analysis techniques are used to answer the hypothesis that: (1) The application of e-SAMSAT has a positive effect on motor vehicle taxpayer compliance. (2) Tax sanctions have a positive effect on motor vehicle taxpayer compliance. (3) Taxation services do not have a positive effect on motor vehicle taxpayer compliance (4) Simultaneous application of e-SAMSAT, tax sanctions and taxation services have a positive effect on motor vehicle taxpayer compliance. Keywords: Implementation of e-SAMSAT; Taxpayer Compliance; Tax Sanctions; Tax Services.